SCOPE AND METHOD OF THEORY AND RESEARCH IN THE MEASUREMENT OF INCOME AND WEALTH. - Gordon, Myron J. (The Accounting Review, 1960)
Accounting theory in the measurement of an economic entity's income and wealth involves the discovery and in some sense the verification of principles or rules which will make the practice of accounting in the actual tasks of measurement more effective. The importance of the task and the inherent fascination of the subject have combined to make this among the most intensively discussed topics in accounting. In fact, some consider it the subject of accounting theory, and refer to the theory underlying the measurement of income and wealth. Broadly speaking, economics is concerned with explaining and predicting the behavior that man engages in to satisfy his material wants, and the behavior or characteristics of physical objects as instruments for the satisfaction of these wants. Topics of interest include such diverse phenomena as the price and output of a commodity, the functioning of trade unions, the impact of seniority and business pension plans on the mobility of workers, the dividend policy of corporations, and the conditions which favor change in the technology of production.